Students’ perception on the effectiveness of internship programme - Rosli, Mohammad Amir Luqman (2018)
The title of this research is “Students’ Perception of Industrial Internship Programme”. The main objective of this research is to identify the relationship between students/s perception factors toward effectiveness of internship programme. The students’ perception factor consists of company support, pre-placement activities and host company’s support which have been identified in order to investigate whether or not these factors have influence toward effectiveness of internship programme. The independent variables in this research are students’ perception factors while dependent variable is effectiveness of internship programme. In order to complete this research, three hypotheses were constructed to determine the relationship between independent variable and dependent variable. From this study, university is able to identify the problems which rely on the level of student’s perception factors and effectiveness of internship programme. This research covers five chapter. Chapter one consists of introduction and background of the research while chapter consist of literature review. Next, chapter three consist of research methodology and chapter four consists of data analysis and interpretation of data. The final chapter which is chapter five, consist of conclusion and recommendation